167 Predicting outcomes in chronic coronary syndromes with high-sensitivity cardiac troponin. (6th June 2022) - Wereski, Ryan; Adamson, PD; Shek Daud, NS; Strachan, Fiona; Taggart, Caelan; Bularga, Anda; Kimenai, Dorien; Bing, Rong; Tuck, Chris; Anand, A; Lowe, DJ; Chapman, Andrew; et al.
Abstract : Introduction: Objective risk stratification based is recommended in all patients with a new diagnosis of stable ischaemic heart disease. However, more than half of patients with chronic coronary syndromes who have a future myocardial infarct do not have obstructive coronary disease on coronary imaging, or the ischaemic substrate to enable effective risk stratification with functional testing. There is need for an effective risk stratification tool that can be applied to all patients with chronic coronary syndrome to help guide management decisions. Purpose: To evaluate the role of cardiac troponin testing in the risk stratification of patients with chronic coronary syndrome.Method: Consecutive patients attending a tertiary cardiac centre for investigation of chronic coronary syndrome with coronary angiography were eligible for enrolment into this prospective observational study. High-sensitivity cardiac troponin I was measured in all patients immediately prior to angiography with clinicians blinded to the results. Troponin concentrations were log transformed and evaluated as a continuous variable in adjusted Cox regression models, and categorised as low (<5 ng/L), intermediate (5 ng/L - 99th centile), or high (>99th centile). The primary outcome was a composite of myocardial infarction or cardiovascular death over a median follow-up of 2.5 years. Results: In total, 4, 344 consecutive patients were enrolled (median age 66 years (IQR 59 - 73), 32.4% female). The majority had obstructive coronary disease on angiography (62.4%, 2, 712/4, 344), with fewer having non-obstructive disease (27.4%, 1, 193/4, 344) or angiographically normal coronary arteries (10.2%, 442/4, 344). Patients with obstructive disease had higher troponin levels (median 4.0 ng/L, IQR 2.1 - 8.6) than those with non-obstructive disease (2.7 ng/L, IQR 1.4 - 5.1; P<0.001). Patients with the highest troponin concentration were most likely to have a primary outcome (62.8 events per 1, 000 patient-years) as compared to those with intermediate (45.5 per 1, 000 patient-years) or low troponin levels (15.1 per 1, 000 patient-years). In patients with obstructive disease, the incidence of the primary outcome was highest in those with the highest troponin (64.5 per 1, 000 patient-years) as compared to those with obstructive disease and either intermediate or low troponin levels (53.2 and 21.2 per 1, 000 patient-years, respectively). After adjusting for coronary disease severity, troponin remained an important independent predictor of the primary outcome (aHR 3.1 95%CI 2.4–3.9). Conclusion: In patients with chronic coronary syndrome, cardiac troponin can reliably identify individuals at the highest risk of myocardial infarction or cardiovascular death. Combined with angiographic indices of disease severity, troponin testing in the chronic coronary syndrome could augment current risk stratification strategies and may inform optimised treatment decisions. Conflict of Interest: None